Effect of antioxidant/reducing agents on the initial and long-term bonding performance of a self-etch adhesive to caries-affected dentin with and without smear layer-deproteinizing. (October 2020) - Prasansuttiporn, Taweesak; Thanatvarakorn, Ornnicha; Mamanee, Teerapong; Hosaka, Keiichi; Tagami, Junji; Foxton, Richard M.; Nakajima, Masatoshi
Abstract: This study aimed to evaluate the effect of a reducing agent containing p -toluenesulfinic acid sodium salt (Accel®) and plant-extract antioxidant (rosmarinic acid solution) on the bonding durability of a self-etch adhesive to caries-affected dentin with and without smear layer-deproteinizing with NaOCl solution. The caries-affected dentin were assigned to pretreatment of smear layer-deproteinizing with NaOCl solution or none, then subdivided to reducing agent/antioxidant treatment with p -toluenesulfinic acid sodium salt or rosmarinic acid solution or none. After bonding with 2-step self-etch adhesive and restoring with resin composite, the specimens were stored in artificial saliva for 24 h or 1 year. The microtensile bond strength (μTBS) were analyzed by three-way ANOVA with post-hoc Tukey's test and t -test ( p  < 0.05). The collagen-fibril status at hybridized complex was observed under TEM. The results showed that μTBS to caries-affected dentin significantly decreased after 1-year of storage ( p  < 0.05). Smear layer-deproteinizing with NaOCl significantly decreased μTBS to caries-affected dentin despite eliminating hybridized smear layer, however a subsequent application with p -toluenesulfinic acid sodium salt and rosmarinic acid solution significantly increased initial bond strengths ( p  < 0.05) and maintained the bond strengths after 1-year of storage ( p  > 0.05), with preservation of collagen-fibril integrity within authentic hybrid layer. Therefore, the additional application of p -toluenesulfinic acid sodium salt and rosmarinic acid solution after smear layer-deproteinizing with NaOCl could improve initial and long-term bond strengths of a self-etch adhesive to caries-affected dentin.